Estimation of the denitrification in the lower Mississippi Valley - Saleh, Abdul Razak (2001)
CREAMS model was developed by a team of the Agricultural Research Service, United States Department of Agriculture scientists JQ simulate the effect of management systems on nonpoint source water pollution. The CREAMS denitrification algorithm is a function of the number of days of drainage from the bottom layer of the profile. The CREAMS denitrification algorithm was modified to account for the high soil moisture conditions by incorporating a water function.The average annual denitrification value simulated by using modified algorithm was higher than the one predicted by CREAMS algorithm.This result is expected because the modified algorithm uses a water function to reflect the degree of soil saturation.